Good Capital and Better World Books. (A), A better world for investing - Jones, Jamie; Yee, Jennifer; Selke, Wes ([London] : SAGE, 2016)
The purpose of this case is to introduce the topic of socially responsible investing from both the investor and investee perspectives. The students will walk away with an understanding of how to evaluate a portfolio company on a social/environmental mission and on traditional financial criteria, as well as understanding what considerations should be top of mind for a social venture considering accepting an equity investment.
Originally Published in: Jones, J., Yee, J., & Selke, W. (2010). Good Capital and Better World Books (A): A Better World for Investing. 5-310-508(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Venture capital -- Case studies; Social responsibility of business -- Case studies; Social entrepreneurship -- Case studies; Investments -- Moral and ethical aspects -- Case studies